Tyrosine kinase inhibitor discontinuation in non-allografted Philadelphia-positive acute lymphoblastic leukemia patients: a Campus ALL real-life study - Matteo Dragani; Michela Ansuinelli; Cristina Papayannidis; Nicola Fracchiolla; Valeria Cardinali; Michele Cedrone; Fabio Guolo; Salvatore Perrone; Prassede Salutari; Elisabetta Todisco; Robin Foà; Sabina Chiaretti (Haematologica)
Not available.